Repeated, Intermittent Social Defeat across the Entire Juvenile Period Resulted in Behavioral, Physiological, Hormonal, Immunological, and Neurochemical Alterations in Young Adult Male Golden Hamsters - Yu, Wei-Chun; Liu, Ching-Yi; Lai, Wen-Sung (Frontiers in Behavioral Neuroscience, 2016)
The developing brain is vulnerable to social defeat during the juvenile period. As complements of human studies, animal models of social defeat provide a straightforward approach to investigating the functional and neurobiological consequences of social defeats. Taking advantage of agonist behavior and social defeat in male golden hamster, a set of 6 experiments was conducted to investigate the consequences at multiple levels in young adulthood resulting from repeated, intermittent social defeats or “social threats” across the entire juvenile period. Male hamsters at postnatal day 28 (P28) were randomly assigned to either the social defeat, “social threat”, or arena control group, and they correspondingly received a series of 9 social interaction trials (i.e., either social defeat, “social threat”, or arena control conditions) from P33 to P66. At the behavioral level (Experiment 1), we found that repeated social defeats (but not “social threats”) significantly impacted locomotor activity in the familiar context and social interaction in the familiar/unfamiliar social contexts. At the physiological and hormonal levels (Experiments 2 & 3), repeated social defeat significantly enhanced the cortisol and norepinephrine concentrations in blood. Enlargement of the spleen was also found in the social defeat and “social threat” groups. At the immunological level (Experiment 4), the social defeat group showed lower levels of pro-inflammatory cytokines in the hypothalamus and hippocampus but higher concentration of IL-6 in the striatum compared to the other two groups. At the neurochemical level (Experiment 5), the socially defeated hamsters mainly displayed reductions of dopamine, dopamine metabolites, and 5-HT levels in the striatum and decreased level of 5-HT in the hippocampus. In Experiment 6, an increase in the spine density of hippocampal CA1 pyramidal neurons was specifically observed in the “social threat” group. Collectively, our findings indicate that repeated, intermittent social defeats throughout entire adolescence in hamsters impact their adult responses at multiple levels. Our results also suggest that the “social threat” group may serve as an appropriate control. This study further suggest that the alterations of behavioral responses and neurobiological functions in the body and brain might provide potential markers to measure the negative consequences of chronic social defeats.